Analisis Bimbingan Kelompok Menggunakan Teknik Role Playing Untuk Mengatasi Perasaan Tidak Percaya Diri Siswa Di SMA Dharma Patra P. Berandan - Nurbaini Nurbaini; Saiful Akhyar Lubis; Abdul Aziz Rusman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to find out: analyze whether there is an influence of group guidance services using role playing techniques on students' lack of self-confidence in class XI IPS 1 SMA Dharma Patra P. Berandan. The subjects of this research were 32 students of class XI IPS 1 Dharma Patra P. Berandan. The sampling technique used purposive sampling. The data for this research was taken using a self-confidence questionnaire with 30 valid and realistic questions, then the data was analyzed using the SPSS test. Pre-test data to overcome feelings of lack of self-confidence obtained an average score of 2.045. Meanwhile, post test data on self-confidence obtained an average score of 3.875. This means that the average score of students after receiving group guidance services using role playing techniques is higher than before receiving group guidance services using role playing techniques. From data analysis it is obtained that Fcount = 15 with a = 0.05 while Ftable = 4. From these data it can be seen that Fcount > Ftable where 15>4. This means that the hypothesis is accepted. Group guidance services using role playing techniques contributed 33.4% to increasing self-confidence for class XI IPS 1 Dharma Patra P. Berandan students. This shows that there is an influence of providing group guidance services using role playing techniques to overcome the lack of self-confidence of class XI IPS 1 Dharma Patra P. Berandan students or the hypothesis can be accepted.